Effect of Various Organic Fertilisers on Phosphorus Mineralisation, Use Efficiency and Maize Yield - Frank Mnthambala; Elizabeth Tilley; Sean Tyrrel; Ruben Sakrabani (Resources, 2022)
When soils are phosphorus (P) deficient, external sources in the form of fertilisers have to be applied to increase crop yields. The world depends on mined sources for P fertilisers, and recent reports indicate that an increase in the human population has led to rising demand for P fertilisers, making its future supply uncertain. A low supply of chemical P fertilisers may lead to food insecurity. Although the efficacy of organic sources of P is unclear, organic waste materials containing P can potentially replace inorganic P sources. Previously, organic fertilisers have been used to supply N and even P, but the application rates were mostly N based, resulting in inconsistent and comparable results. This research was conducted to understand P mineralisation and the availability of the P-based organic fertilisers. The results showed that available P in the soil at 3 weeks accounted for 50%, 6 weeks accounted for 49%, and 9 weeks counted for 46% of the maize yield. The organic P sources maintained soil available P above the threshold available P value in Malawi. The P sources did not affect the maize P use efficiency (PUE). The results indicate that organic P sources could be used as an alternative fertiliser for maize production in Malawi.